Study Of Comparative Methods Of Flexible Pavement And Rigid Pavement - Alfikri Alfikri; Hendra Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Road widening improvement works at the border of Inhu regency – Simpang Japura is the successor road improvement works at Lintas Timur Riau – Jambi road KM 171+700 – 172+790 along 1670 m with 7.6 m width. This research is to analyze the cost differences between flexible and rigid pavement construction works. The construction design for flexible pavement is using component analysis 1987 method and Pd T-12-2003 (Bina Marga Method) for rigid pavement method. The data which needed for analyze is LHR, the value of subgrade CBR test, Inhu district unit price in 2015. The calculation result for each layer of flexible pavement as follow, theaggregate class B thickness for the bottom foundation is 50 cm, class A aggregates for the top foundation surface for is 20 cm, and top layer Laston is 10 cm (AC-BC 6 cm and AC-WC 4 cm)with asphalt prime coat 0.8 liter/m2 and adphalt take coat 0.25 liter/m2. The calculation result for each layer of rigid pavement as follow, the aggregate class A thickness is 25 cm, bottom foundation layer is 15 cm, and hard concrete pavement is 30 cm (min 21 cm), with transverse reinforcement using Ø 32, longitudinal reinforcement D16, and concrete class K-250 for the road sideway. This analyst result taken the construction cost for each method as follow the flexible pavement needed Rp 14.092.817.312,79 to construct and hard pavement Rp. 17.658.141.077,05. The cost deviation between the both methods is Rp. 3.565.323.764,26 or 20,19 %.Keywords: Flexible Pavement, Rigid Pavement, Budget Planning, Cross-East